Sing, Aretha, sing! : Aretha Franklin, "Respect," and the civil rights movement - Abdurraqib, Hanif, 1983-; Evans, Ashley (New York : Farrar Straus Giroux Books for Young Readers, 2021)
"An empowering picture book biography of Aretha Franklin and her role in civil rights, perfect for Women's History Month and Black History Month"--.
Grades 2-3
Keywords: Franklin, Aretha -- Juvenile literature; Soul musicians -- United States -- Biography; African American singers -- Biography -- Juvenile literature; Singers -- United States -- Biography -- Juvenile literature; Civil rights movements -- United States -- 20th century -- Juvenile literature